Cumulative mild head injury in rugby: cognitive test profiles of professional rugby and cricket players - Ancer, Ruth Lauren (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
This study investigates the effects of cumulative concussive and subconcussive mild head injury on the cognitive functioning of professional rugby players. A comprehensive battery of neuropsychological tests was administered to 26 professional rugby players and a noncontact sport control group of 21 professional cricket players. The test performances of the rugby players were compared to those of the cricket players. Within the rugby group, forward and backline players were compared. An analysis of mean score differences between the rugby and cricket group failed to support the presence of brain damage effects in the rugby group. However, there was significantly increased variability of scores for the rugby players compared with the cricket players on tests particularly sensitive to cognitive deficit associated with mild head injury. This invalidates the null indications of average effects, indicating that a notable proportion of rugby players' performances were falling off relative to the rest of the rugby players on tests vulnerable to the cognitive effects of diffuse brain damage. Mean score comparisons within the rugby group indicated that it was the subgroup of forward players, in particular, whose test performances revealed deficits suggestive of cerebral damage. Specifically, deficits were found in working memory, visuoperceptual tracking, verbal memory and visual memory, a pattern of deficits commensurate with cumulative mild head injury. The theoretical perspectives of Satz's (1997) Brain Reserve Capacity Theory and Jordan's (1997) 'Shuttle' model of variability are drawn upon in order to elucidate research findings and suggestions for future research are provided.
Keywords: Head -- Wounds and injuries; Rugby football injuries; Cricket injuries; Cognitive therapy; Neuropsychological tests